Manifestation of global seismic activity in the atmosphere and ionosphere - Zakharov, I. G.; Chernogor, L. F. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2020)
Background. In recent decades, the concept of earthquakes (EQ) has been formed as the final stage of a planetary continuous self-organizing process with periods of accumulation and relaxation of tectonic stresses. However, in the scientific literature, as before, studies of the response of atmospheric and ionospheric processes to individual strong EQs are presented. In this work, the coupling of processes in the lithosphere, troposphere and ionosphere is considered for the first time, taking into account new ideas about the seismic process against the background of processes caused by space weather, which is a new step in the study of the human environment.Objectives of the work is to find relationships in the Earth – atmosphere – ionosphere – magnetosphere system on a planetary scale with a change in global seismic activity (GSA).Materials and methods. The studies were carried out using four daily databases for 2007–2015 on space weather and the magnetosphere (solar and geomagnetic activity indices), the ionosphere (f0F2 is the critical frequency of the F2 region in the western and eastern hemispheres; TEC is the global ionospheric total electron content), the surface atmosphere (atmospheric pressure) and the lithosphere (maximum EQ amplitude per day). The method of superimposed epochs and other statistical methods of analysis were used.Results. Quasi-synchronous changes in magnetospheric, ionospheric, and tropospheric characteristics have been established during periods of a sharp increase in GSA. They often have a cyclical sawtooth character from one seismically active period to another, which indicates the possibility of continuous interaction of geospheres, and not only during periods of disturbances. In particular, an increase in f0F2 with a sharp increase in GSA by up to 0.5 MHz was found almost simultaneously in the eastern and western hemispheres.Conclusions. The results obtained indicate the possibility of long-term or continuous interaction of the lithosphere with the geospheres located above. Space weather changes can be one of the sources of synchronization. As a possible mechanism for the appearance of global effects in the atmosphere and ionosphere when the GSA changes, it is proposed to consider the role of the release of deep gases to the surface. This process is global and is associated simultaneously with both seismicity and the parameters of the Earth's rotation.